2022
DOI: 10.1108/ijchm-12-2021-1478
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of empirical studies of pro-environmental behavior in hospitality and tourism contexts

Abstract: Purpose The purpose of this study was to gain a holistic view of pro-environmental behavior (PEB) among hospitality and tourism consumers through a systematic review of empirical studies. Based on this comprehensive review, this study demonstrates how the literature has been created and has evolved over time, thereby providing proposals for future research agendas. Design/methodology/approach The preferred reporting items for systematic reviews and meta-analyses method was used as a rigorous searching method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(11 citation statements)
references
References 121 publications
0
11
0
Order By: Relevance
“…Therefore, activating TERB is crucial to mitigating the negative impact of tourism on the natural environment. However, the causes of TERB are complex and there are many factors that influence TERB [ 63 ].In this study, on the basis of self-regulated attitude theory, destination attractiveness was selected as the variable of tourists’ evaluation of a destination, and it was measured using the two elements of facility service attractiveness and sightseeing experience attractiveness. In addition, place attachment was introduced as the variable for tourists’ emotional responses, and the response behavior of tourists was reflected by TERB.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, activating TERB is crucial to mitigating the negative impact of tourism on the natural environment. However, the causes of TERB are complex and there are many factors that influence TERB [ 63 ].In this study, on the basis of self-regulated attitude theory, destination attractiveness was selected as the variable of tourists’ evaluation of a destination, and it was measured using the two elements of facility service attractiveness and sightseeing experience attractiveness. In addition, place attachment was introduced as the variable for tourists’ emotional responses, and the response behavior of tourists was reflected by TERB.…”
Section: Discussionmentioning
confidence: 99%
“…Also, research claims that a strong sense of self‐identification can be developed through network exposure (Kim, 2018; Wang, Van der Werff, et al, 2021). Social network research has consistently demonstrated self‐identification as an affordance that enables desirable behaviours (Lin, Xu, & Wang, 2022; Lin, Zhu, et al, 2022; Wang & Chen, 2021). In this way, GSN may also enable green self‐identification, as individuals will be able to psychologically connect with the messages shared in specific green online communities (Dickinson et al, 2017) and vertical networks 3 like Care2 (http://www.care2.com).…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…Finally, the current research utilizes a convergence of the SIT and the S‐O‐R framework to explicate the relationship between GSNs and PEB. However, as suggested by recent review studies (for instance, Lin, Xu, & Wang, 2022; Lin, Zhu, et al, 2022; Paul & Bhukya, 2021), diverse theoretical approaches (e.g., the prospect theory and the technology adoption model) hold pertinence in the PEB domain, and so utilizing these will pave the way for further insights into the GSNs–PEB relationship. Also, given that a singular approach to the application of theory has been predominantly utilized by prior research (Lin, Xu, & Wang, 2022; Lin, Zhu, et al, 2022; Xiao et al, 2023), the integrated theoretical lens utilized by this study will serve as a guiding platform for future enquiry into the subject.…”
Section: Implications Limitations and Future Directionsmentioning
confidence: 99%
“…In a systematic review of 234 empirical studies, Lin et al (2022) identified about 30 antecedents of pro-environmental behaviors among consumers, such as willingness to choose or recommend a green hotel or restaurant, pay more, reduce waste and use/recommend transportation with less pollution. For example, consumers’ environmental concerns, attitudes, awareness and self-identify can significantly influence consumers’ pro-environmental behaviors.…”
Section: Literature Reviewmentioning
confidence: 99%